2013
DOI: 10.1177/0333102413477741
|View full text |Cite
|
Sign up to set email alerts
|

Functional and effective connectivity in EEG alpha and beta bands during intermittent flash stimulation in migraine with and without aura

Abstract: There were clear differences in ongoing EEG under visual stimulation, which emerged between the two forms of migraine, probably subtended by increased cortical activation in migraine with aura, and compensatory phenomena of reduced connectivity and functional networks segregation, occurring in patients not experiencing aura symptoms. Further investigation may confirm whether the clinical manifestation of aura symptoms is subtended by a peculiar neuronal connectivity pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 44 publications
(65 reference statements)
4
62
2
Order By: Relevance
“…In a preliminary study, individuals who had migraine without aura showed increased phase synchronization in the alpha band and reduced connectivity during intermittent flash stimula tion, whereas those who had migraine with aura dis played clear desynchro nization in the beta frequency range and increased connectivity during visual stimula tion ( Figure 1). 25 Given that brain activation is now described in terms of increased connectivity of different functional brain networks, visual stimulation seems to induce a more vigorous cortical activation and spread of information in migraine with aura than in migraine without aura (which is charac terized by weak interaction between cortical regions), possibly because of a prevalent resonance of rhythmic activity generated at subcortical and thalamic levels. 22 Evoked responses to non-noxious stimuli…”
Section: Increased Synchronizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In a preliminary study, individuals who had migraine without aura showed increased phase synchronization in the alpha band and reduced connectivity during intermittent flash stimula tion, whereas those who had migraine with aura dis played clear desynchro nization in the beta frequency range and increased connectivity during visual stimula tion ( Figure 1). 25 Given that brain activation is now described in terms of increased connectivity of different functional brain networks, visual stimulation seems to induce a more vigorous cortical activation and spread of information in migraine with aura than in migraine without aura (which is charac terized by weak interaction between cortical regions), possibly because of a prevalent resonance of rhythmic activity generated at subcortical and thalamic levels. 22 Evoked responses to non-noxious stimuli…”
Section: Increased Synchronizationmentioning
confidence: 99%
“…This phenomenon might be subtended by increased cortical activation in migraine with aura during visual stimulation. The figure is based on data from a study by de Tommaso et al 25 effect on habituation profiles. 66,67 Finally, spontaneous clinical worsening or improvement of attack frequency can influence the baseline level of thalamocortical activa tion 68,69 and, hence, the degree of habituation in patients with migraine.…”
Section: Impaired Habituationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study [14] we observed increased causal connections across 6 scalp derivations in beta band in MWA patients compared with both MWoA and controls under intermittent flash stimulation, suggesting a different pattern of visual stimuli processing and cortical activation modality in patients experiencing aura symptoms. A recent FMRI study confirmed a spread of cortical activation in MWA patients during a visual task [15].…”
Section: Introductionmentioning
confidence: 72%
“…Besides overt classification differences between migraine with (MA) and without aura (MO) (International Headache Society, 2004), few neurophysiological studies have compared these two entities (Coppola et al, 2007;de Tommaso et al, 2013). When considered both together, the most consistent finding was a defective habituation of pattern reversal-visual evoked potentials (PR-VEPs) (Schoenen, 2006).…”
Section: Introductionmentioning
confidence: 99%